Avaliação da biodistribuição e da toxicidade aguda in vivo de lipossomas pH-sensíveis de circulação prolongada contendo doxorrubicina - Juliana de Oliveira Silva (2016)
Doxorubicin (DOX) is an anthracyclic antineoplastic agent widely used on control of solid tumors, however, severe side effects of this drug, especially severe and sometimes irreversible cardiotoxicity, has limited the DOX use. In this context, the use of liposomes resposive to pH variation has shown a promising strategy to specific delivery of cytotoxic drugs into the tumor. Preclinical studies of biodistribution and acute toxicity are critical steps in pharmaceuticals development. This studies can determine the routes of elimination and accumulation of this new product, allowing to infer data related to activity and possible toxicity targets. Therefore, the aim of this study was evaluate the biodistribution and in vivo acute toxicity of doxorubicin pHsensitive, prolonged circulation liposome. In vivo studies were approved by the Ethics Committee on Animal Use with protocol number (302/14). To the biodistribution study, DOX was labeled with radioisotope technetium-99m and was encapsulated in pHsensitive liposomes (SphI-DOX-99mTc) and not pH-sensitive liposomes (nSpHL-DOX99m Tc). Liposomes were obtained with particle size, zeta potential, encapsulating percentage and lekeage profile expected and suitable for intravenous (IV). The pHsensitivity was confirmed in vitro. SphI-DOX-99mTc and nSphI-DOX-99mTc showed the same blood clearance profile in healthy females Balb/c mice, however, SphI-DOX99m Tc showed area under curve 1.36 times higher than nSphI-DOX-99mTc. SphI-DOX99m Tc and nSphI-DOX-99mTc showed expected biodistribution in mice with 4T1 tumor cells. Was observed radiation accumulation in liver and spleen. There was higher accumulation of SphI-DOX-99mTc in the tumor. To toxicity studies, healthy mice were treated with DOX and SpHL-DOX (10, 15, and 17.5 mg/kg) in single dose intravenously and they was observed for 14 days. There was 100% of mortality of the animals treated with 17.5 mg/kg DOX. After 14 days, the animals were euthanized and blood and organ collected for haematological, biochemical and histopathological tests. It was observed protective effect in kidney, heart and liver of animals treated with SpHL-DOX because of morphological, biochemical and electrocardiographic changes significantly lower when compared to animals treated with doxorubicin. In conclusion, pH-sensitive liposomes promote higher DOX accumulation in the tumor and its use can reduce the systemic toxicity of this drug.